GEOSTRATEGY FOR A COUNTRY'S INTERNATIONAL POLICY - Rahmat, Rahmat; Umar, Harun; Anderson, Christopher J. (DIVERSITY Logic Journal Multidisciplinary, 2025)
Background. In foreign policy, geostrategies are employed to help a nation overcome international obstacles and uphold its objectives. Research Purpose. This research examines geostrategy for a country’s international policy. Research Method. This study uses a literature study method with a qualitative-descriptive approach. The study focuses on how nations develop their geostrategies, the internal and external variables that affect foreign policy, and the intimate connection between geopolitical strategies and state goals in terms of social, political, economic, and security. Findings. Reasonable and adaptable geostrategic tactics enable a country to respond effectively to global dynamics, whether political, economic, or security. With a flexible and realistic strategy, a country can strengthen its bargaining position on the international stage, build mutually beneficial cooperation, and minimize the potential for conflict. Ultimately, the implementation of adaptive geostrategy plays a crucial role in maintaining national stability while promoting prosperity and sustainable development. Conclusion. It is envisaged that this research would aid in our comprehension of geostrategy dynamics and provide a useful framework for international policy-making.